2014
DOI: 10.1007/s12687-014-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

To worry or not to worry: breast cancer genetic counseling communication with low-income Latina immigrants

Abstract: The purpose of this pilot study was to describe communication practices during hereditary breast cancer genetic counseling (GC) with low-income immigrant Latina patients in a public hospital setting. We utilized qualitative ethnographic methods, including direct observation of GC appointments with Latina patients at a public hospital offering free GC and BRCA testing and in-depth qualitative interviews with patients after they had received their BRCA genetic test results. Twenty-five patients participated; 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 35 publications
3
42
3
Order By: Relevance
“…Coders included the first author, a bilingual bicultural (Cantonese/Chinese) social psychologist, and bilingual/bicultural (Spanish/Latina) research associate and the PI, a medical anthropologist. Coders independently reviewed the initial transcripts using a combination of open coding and a priori codes based on the interview guide, the literature, and preliminary research (Joseph and Guerra 2015). Coders then met to reconcile discrepancies and establish a codebook.…”
Section: Discussionmentioning
confidence: 99%
“…Coders included the first author, a bilingual bicultural (Cantonese/Chinese) social psychologist, and bilingual/bicultural (Spanish/Latina) research associate and the PI, a medical anthropologist. Coders independently reviewed the initial transcripts using a combination of open coding and a priori codes based on the interview guide, the literature, and preliminary research (Joseph and Guerra 2015). Coders then met to reconcile discrepancies and establish a codebook.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a fine line between the liberty to translate in a close and culturally meaningful way, and translating information that was not originally conveyed. Joseph and Guerra (2015) found that the technical information of cancer genetic counseling appointments caused professional Spanish interpreters to translate meaning and facts of statements incorrectly. Since the Hmong language does not, by its very structure, allow for word-to-word translation of genetic terms and concepts, any translation from English to Hmong has the potential to be different than intended by the counselors.…”
Section: Education: Graduate Training and Continuing Educationmentioning
confidence: 99%
“…As such, the increasing linguistic diversity in the U.S., and the accompanying cultural diversity, present a challenge for genetic counselors (GCs) (Lewis 2002;Ota Wang 2001;Weil and Mittman 1993). The possibility of genetic counseling services that may lead to inappropriate screening or treatment due to language barriers is a serious concern (Bhogal and Brunger 2010; Joseph and Guerra 2015).…”
Section: Introductionmentioning
confidence: 99%